Pemikiran dan Kebijakan Nahdlatul Ulama dalam Menjaga Kedaulatan Wilayah Negara Kesatuan Republik Indonesia pada Era Reformasi (1998-2009) - Zudi Setiawan (SPEKTRUM, 2010)
AbstractIn the 1998-2009 period, Indonesia is in the multidimensional crisis conditions and the threat of a split in the (disintegration) of the nation and also the threat appears to come from outside such as claims or annexation of the small islands of Indonesia by other countries. In the course of the history of thought and policy of NU in the reform era (1998-2009) shows that NU plays an important role in maintaining the sovereignty of the Unitary Republic of Indonesia territory. National ideology which is owned by the NU was based on a religious basis in addition to all the objective conditions of the nation and a pluralistic nation of Indonesia. National ideology is what makes NU known as a nationalist Islamic organization. From the ideological basis of nationality is also the NU at the forefront in safeguarding the sovereignty of the Republic of Indonesia territory.Key Words : Nahdlatul Ulama, Thought, Policy, Nationalism, the sovereignty of the Republic of Indonesia territory